2015
DOI: 10.1007/s00380-014-0625-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intravascular ultrasound findings on long-term patency after self-expanding nitinol stent implantation in the iliac artery lesion

Abstract: Although intravascular ultrasound (IVUS) predictors of stent patency for the coronary artery lesion have been established, little is known about IVUS predictors of stent patency for the aorto-iliac artery lesion. We analyzed 154 lesions of 122 patients who underwent stent implantation for iliac artery lesions. Quantitative and qualitative IVUS analyses were performed for pre- and post-procedural IVUS imaging in all lesions. Target lesion revascularization (TLR) was defined as clinically driven revascularizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Because previous studies have not shown an association between thrombotic lesions and poor dilation before and after stenting can be another cause of restenosis. IVUS analyses, after stent implantation, in the iliac artery lesions showed that the postprocedural minimum stent area might predict longterm stent patency 20) . In our study, the frequency of direct stenting was high, and the frequency of poststenting balloon dilation was low in the thrombotic coronary optical coherence tomography analyses have shown that post-stent, irregular tissue protrusions are associated with subsequent neo-atherosclerosis after stent implantation 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies have not shown an association between thrombotic lesions and poor dilation before and after stenting can be another cause of restenosis. IVUS analyses, after stent implantation, in the iliac artery lesions showed that the postprocedural minimum stent area might predict longterm stent patency 20) . In our study, the frequency of direct stenting was high, and the frequency of poststenting balloon dilation was low in the thrombotic coronary optical coherence tomography analyses have shown that post-stent, irregular tissue protrusions are associated with subsequent neo-atherosclerosis after stent implantation 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported multiple lesion characteristics and insufficient stent enlargement and edge dissection as being associated with unacceptable limb patency. [18][19][20][21] All of these factors can cause low SFA flow velocity, which EVT is supposed to improve. When EVT is performed in patients with PAD, limb patency is affected by the endpoint of EVT.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Factors related to EVT characteristics, such as insufficient stent enlargement and edge dissection, have also been reported to affect primary patency. 20,21 However, it is unknown why these factors lead to worse outcomes. We hypothesized that patency failure was ultimately related to lower flow velocity in the affected arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that female sex, diabetes mellitus, chronic kidney disease, small reference diameter, lesion length, post minimum lumen area, stent edge dissection, lesion calcification, and stent use are independent predictors of restenosis of EVT for the AI artery …”
Section: Introductionmentioning
confidence: 99%